Determining significant factors affecting green building price using multiple regression analysis / Nur Syafiqah Jamil, Thuraiya Mohd and Suraya Masrom - Jamil, Nur Syafiqah; Mohd, Thuraiya; Masrom, Suraya (Universiti Teknologi MARA, Perak, 2020)
The green building (GB) can be defined as the method of increasing the efficiency of the building and site. However, the spillover effect of GB price in Malaysia has not widely been discovered as there are limited case studies on this issue. This paper attempts to determine the significant factors that influence the GB price. The empirical experiment has been conducted to test the Multiple Regression Analysis (MRA) model on a real dataset of house prices in the area of Klang Valley, Selangor with GB specifications. The result showed that factors related to tenure have significant contributions to the GB price.